Angiotensin-Converting Enzyme ID Polymorphism in Patients with Heart Failure Secondary to Chagas Disease - Silva,Silene Jacinto da (2017)
Abstract Background: Changes in the angiotensin-converting enzyme (ACE) gene may contribute to the increase in blood pressure and consequently to the onset of heart failure (HF). The role of polymorphism is very controversial, and its identification in patients with HF secondary to Chagas disease in the Brazilian population is required. Objective: To determine ACE polymorphism in patients with HF secondary to Chagas disease and patients with Chagas disease without systolic dysfunction, and to evaluate the relationship of the ACE polymorphism with different clinical variables. Methods: This was a comparative clinical study with 193 participants, 103 of them with HF secondary to Chagas disease and 90 with Chagas disease without systolic dysfunction. All patients attended the outpatient department of the General Hospital of the Federal University of Goias general hospital. Alleles I and D of ACE polymorphism were identified by polymerase chain reaction of the respective intron 16 fragments in the ACE gene and visualized by electrophoresis. Results: In the group of HF patients, 63% were male, whereas 53.6% of patients with Chagas disease without systolic dysfunction were female (p = 0,001). The time from diagnosis varied from 1 to 50 years. Distribution of DD, ID and II genotypes was similar between the two groups, without statistical significance (p = 0,692). There was no difference in clinical characteristics or I/D genotypes between the groups. Age was significantly different between the groups (p = 0,001), and mean age of patients with HF was 62.5 years. Conclusion: No differences were observed in the distribution of (Insertion/Deletion) genotype frequencies of ACE polymorphism between the studied groups. The use of this genetic biomarker was not useful in detecting a possible relationship between ACE polymorphism and clinical manifestations in HF secondary to Chagas disease.